2021
DOI: 10.3390/ijms22136686
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Vitamin D Modulate Inflammation and Autophagy during Adipose-Derived Stem Cell Differentiation

Abstract: Adipose-derived stem cells (ADSCs) came out from the regenerative medicine landscape for their ability to differentiate into several phenotypes, contributing to tissue regeneration both in vitro and in vivo. Dysregulation in stem cell recruitment and differentiation during adipogenesis is linked to a chronic low-grade inflammation and macrophage infiltration inside the adipose tissue, insulin resistance, cardiovascular disease and obesity. In the present paper we aimed to evaluate the role of metformin and vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…It should be noted that blockade of AMPK signaling could not entirely rescue metformin-inhibited expression of Cidec. These data suggest that metformin might decrease Cidec expression via other pathways, such as inflammation and autophagy [ 78 , 79 , 80 ], integrin/ERK pathway [ 81 ], AKT, and MAPK pathways [ 41 , 55 ] The more details of metformin inhibition on Cidec expression still need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that blockade of AMPK signaling could not entirely rescue metformin-inhibited expression of Cidec. These data suggest that metformin might decrease Cidec expression via other pathways, such as inflammation and autophagy [ 78 , 79 , 80 ], integrin/ERK pathway [ 81 ], AKT, and MAPK pathways [ 41 , 55 ] The more details of metformin inhibition on Cidec expression still need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 1,25(OH) 2 D 3 /VDR signalling suppressed differentiation of 3T3-L1 white adipocytes together with increased expression of uncoupling proteins (Ucp1 and Ucp2) and development of BAT [ 48 ] . Within this context, we previously evaluated the ability of the two molecules to modulate adipogenic differentiation, finely tuning the inflammatory response, cytokines secretion and autophagy [ 38 ] In the present paper we evaluated for the first time, the effect of these molecules in inducing a different phenotype during ADSC adipogenic differentiation. In addition to white and brown adipose tissue, beige or brite adipocytes also have a role in body glucose regulation and thermogenesis [ 49 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overweight and obesity are often associated with Vitamin D deficiency [ 36 ] . Within this context, we previously demonstrated that the combination of vitamin D and metformin is able to counteract ADSC adipogenic differentiation, modulating vitamin D metabolism and the expression of specific epigenetic factors [ 37 , 38 ] . In the present paper, we aimed at evaluating the capability of these two molecules in orchestrating stem cell differentiation towards the beige phenotype, with particular attention to the main adipogenic markers and UCP1 expression, as a potential therapeutic strategy to counteract obesity.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins tend to induce proliferation and angiogenesis and can protect against vascular ED (12). Furthermore, ASCs function in reducing autophagy to treat diabetic nephropathy and inflammation by secreting exosomes and via differentiation (13,14). However, the erectile-protective function of ASCs in treating DMED rats has not yielded satisfactory results and has not yet been applied in clinical work (15).…”
Section: Introductionmentioning
confidence: 99%